2002
DOI: 10.1177/0148607102026006357
|View full text |Cite
|
Sign up to set email alerts
|

Body cell mass repletion and improved quality of life in HIV‐infected individuals receiving oxandrolone

Abstract: This is the first study involving oxandrolone therapy in HIV infection to document changes in quality of life and BCM, the metabolically active component of lean body mass that reflects nutritional status better than other more global body composition parameters. Nutritional status and quality of life can improve in HIV-infected individuals receiving a combined therapeutic approach that includes oxandrolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 25 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…14,15 Most studies of the efficacy of the oral androgen, oxandrolone (OX), have been small, observational, or remain unpublished. [16][17][18][19] The only published randomized clinical trial of OX alone was conducted early in the epidemic for persons with wasting and significant muscle weakness. 20 In this group with myopathy, weight increased with the use of OX but strength did not and there were no measures of body composition.…”
mentioning
confidence: 99%
“…14,15 Most studies of the efficacy of the oral androgen, oxandrolone (OX), have been small, observational, or remain unpublished. [16][17][18][19] The only published randomized clinical trial of OX alone was conducted early in the epidemic for persons with wasting and significant muscle weakness. 20 In this group with myopathy, weight increased with the use of OX but strength did not and there were no measures of body composition.…”
mentioning
confidence: 99%
“…The internal consistency of the total scale in these studies was invariably excellent (Cronbach’s α range 0.91–0.92) [17, 22, 3032]. The subscale α coefficients ranged from 0.72–0.92 with the exception of the cognitive function (CF) domain in two studies from South Africa whose α coefficients were slightly below the recommended 0.70 (Cronbach’s α values of 0.65 and 0.60) [13, 17, 22, 3033]. None of these seven studies reported the test-retest reliability of the FAHI.…”
Section: Resultsmentioning
confidence: 99%
“…The variations with time of FFM, ECW and TBW measured by Tefal and Xitron in AN subjects during monitoring for periods of several weeks were in good agreement. While the BCM is a good indicator of nutritional status [22], it is important to normalize it with respect to H 2 in order to discriminate between AN subjects and a normal population independently of their age.…”
Section: Discussionmentioning
confidence: 99%